Hubungan Pengetahuan dan Sikap Terhadap Perilaku Seks Bebas: Relationship of Knowledge and Attitude to Free Sex Behavior - Astuti, Haryati (Universitas Muhammadiyah Sidoarjo, 2017)
Survey result show that there has happened the increase number of teenagers who do free sex before marriage. That big ammount is a serrious threat to family, society and nation. This research aims at confirming the correlation between knowledge and attitude to the free sex behavior of senior high school teenagers. This research used analytic research design and cross sectional approach by population of all students of X,XI and XII grade as many as 560 graders. The sample was taken by 100 respondents using simple random sampling technique this research was done on may 2016 by using questionnaire sheets. It was done at SMAN 01 Tembilahan. While the data analyzed by using univariate and bivariate analysis with chi-Square Test. The result show that 47%s students have good knowledge, 79% of them have negative attitude to free sex, and 61% have less good behavior. The test result show that there is a corelation between knowledge and free sex behavior, the score of “p value” is 0,016 and there is a correlation between attitude ti the free sex behaviou, the score of “p value” is 0,035. There is a correlation between knowledge and attitude to the free sex behavior. This research result expected can be used as suggestion to prevant the increase of free sex before marriage. And for the next researchers can research another varriable which are maybe give impact to the teenagers free sex behaviour.